NEW RURALITY AND EDUCATION IN AMERICA LATINA CHALLENGES FOR THE TEACHER TRAINING - Miranda Camacho, Guillermo (2012)
This article has as purpose analyze some of the principal curriculum contents, which should be taken into consideration for plans and training for rural teachers in the context the paradigm of new rurality and territorial focus in Latin America. The analytical approach is made from a critical hermeneutics view, examining the connection between structural change processes that have taken place in rural areas in Latin America and emerging educational demands.